MODEL WRITTEN TEXTS IN THE RECOMMENDED SENIOR HIGH SCHOOL ENGLISH TEXTBOOKS - Dwi Rukmini (TEFLIN, 2009)
Abstract: This article is based on the study on the model written texts provided in the Senior High School English textbooks. It is aimed at finding out whether those models are written by considering the English two contexts, cultural and situational, which encircle them. The data are all written texts provided in the six recommended English textbooks published by six different publishers. The results reveal that only eleven out of 115 model written texts tend to be incompatible with the two contexts encircling them, this implies that 104 of them (93.43%) are likely to be compatible and can be used as model texts.